REDUCING WASTE DENGAN MENGGUNAKAN PENDEKATAN LEAN MANUFACTURING - Akhmad Jakfar; Wahyu Eko Setiawan; Ilyas Masudin (Universitas Ahmad Dahlan Indonesia, 2015)
PT. XYZ is one of some cigarette companies in Indonesia. In producing cigarette, the firm requires a material named â€œetiketâ€ which is produced by printing division for internal consumers of PT. XYZ. merupakan salah satu dari beberapa produsen rokok di Indonesia yang telah dikenal masyarakat. In order to produce â€œetiketâ€, there are some wastes occurred. One of wastes occurred in printing division is product defects. This paper attempts to identify wastes in the division of printing using Lean Manufacturing approach by applying Value Stream Mapping (VSM) method. The results from Cause Root analysis found that the problems caused the defects in production process. It shows that the most wastes occurs in the printing division are product defect and waiting time. The product defects are caused because there is no standard applied in processing the product and poor inspections by management, while the causes of waiting time wastes is because of lack of carrier and no standard in each process. The recommendation can be suggested to the company are adding some carrier (productâ€™s transporter), creating process standard in each process. Keywords : Lean Manufacturing, Value Stream Mapping, Value Stream Analysis.